Fertility characteristics and family planning methods used by women delivering at a University Hospital in Eastern Turkey - Pirincci, E.; Polat, A.; Kumru, S.; Koroglu, A. (Taylor & Francis Inc, 2010)
The aim of this study was to assess the fertility characteristics and family planning methods in the city of Elazig, Turkey. This cross-sectional descriptive study included all the women who had delivered babies at the Elazig Firat Medical Center Obstetrics and Gynecology Clinic. Across the entire group, the mean number of pregnancies was found to be 2.98 +/- 1.89. Among the family planning methods used, the first choice of most women was the condom, which ranked first with 32.2%; the oral contraceptive ranked second with 15.1%. The question, 'Have you ever used any contraceptive methods?' was asked and 55.4% answered 'yes'. The most common method was condom use. The most common method of contraception used by married women for the first time was the condom, and the most common method used during marriage was, again, the condom.
Keywords: Contraceptive method; fertility; Turkey